Proud sorrows - Benn, James R. (Benn, James R. Billy Boyle World War II mystery., 2023)
"Norfolk, England, November 1944: After a series of dangerous missions in the South of France, US Army Captain Billy Boyle is finally on leave, and is settling into a peaceful rest at the country estate of Sir Richard Seaton, the father of Billy's British lover, Diana. Seaton Manor is a comfortable haven, and Billy is eager to spend a few precious days in Diana's company pretending the war is far away. Unfortunately, Billy's leave is cut short when a crashed German bomber resurfaces off the coast with the corpse of a British officer in the pilot seat. The nearby village of Slewford hosts a top-secret military intelligence operation, home to high-ranking German POWs, and so the crash is a matter of national security. Billy is assigned by the commander of the POW facility to investigate. After the plane is discovered, a local villager is murdered-and suddenly what had appeared to be a failed enemy military operation takes on an even more sinister aspect. All Billy's ex-Boston cop instincts are put to the test as he interviews the grieving, angry, and conniving citizens of this idyllic English country village in search of the truth"--